Diverse arrestin-recruiting and endocytic profiles of tricyclic antipsychotics acting as direct α2A adrenergic receptor ligands. (April 2017) - Cottingham, Christopher; Che, Pulin; Zhang, Wei; Wang, Hongxia; Wang, Raymond X.; Percival, Stefanie; Birky, Tana; Zhou, Lufang; Jiao, Kai; Wang, Qin
Abstract: The therapeutic mechanism of action underlying many psychopharmacological agents remains poorly understood, due largely to the extreme molecular promiscuity exhibited by these agents with respect to potential central nervous system targets. Agents of the tricyclic chemical class, including both antidepressants and antipsychotics, exhibit a particularly high degree of molecular promiscuity; therefore, any clarification of how these agents interact with specific central nervous system targets is of great potential significance to the field. Here, we present evidence demonstrating that tricyclic antipsychotics appear to segregate into three distinct groups based upon their molecular interactions with the centrally-important α2A adrenergic receptor (AR). Specifically, while the α2A AR binds all antipsychotics tested with similar affinities, and none of the agents are able to induce classical heterotrimeric G protein-mediated α2A AR signaling, significant differences are observed with respect to arrestin3 recruitment and receptor endocytosis. All antipsychotics tested induce arrestin3 recruitment to the α2A AR, but with differing strengths. Both chlorpromazine and clozapine drive significant α2A AR endocytosis, but via differing clathrin-dependent and lipid raft-dependent pathways, while fluphenazine does not drive a robust response. Intriguingly, in silico molecular modeling suggests that each of the three exhibits unique characteristics in interacting with the α2A AR ligand-binding pocket. In addition to establishing these three antipsychotics as novel arrestin-biased ligands at the α2A AR, our findings provide key insights into the molecular actions of these clinically-important agents. Highlights: A conformational two-state mechanism for proton pumping complex I is proposed. The mechanism relies on stabilization changes of anionic ubiquinone intermediates. Electron-transfer and protonation should be strictly controlled during turnover.